Dampak Game Online Bagi Penggunanya - Doni, Fahlepi Roma (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - With the advancement of the times, technology is also developing, especially application technology is growing rapidly, infrastructure can support the creation of a reliable system too. As for online game technology or offline games, games are not only favored by children, even teenagers and adults who are playing the game. But behind the presence of this game there will be an impact and not good for the user behavior. A real and destructive impact is that the user will forget the time. Game users will be addicted, change behavior so that they become lazy or lie. Innovation results in developing applications have shortened the age limit of the use of software and the use of previous hardware. The creation of games brings reality that can have a good (positive) and unfavorable (negative) effect for game users. This research is to analyze or find out and then examine the impact and behavior of online game users, especially in adolescents. Keywords: Game online